84. Clarifying the Congenital Zika Syndrome Phenotype and Expanding to Congenital Zika Spectrum in the Absence of Laboratory Evidence. (31st December 2020) - Zambrano, Laura D; Delaney, Augustina; Rose, Charles E; Gilboa, Suzanne; Tong, Van; Valencia-Prado, Miguel; Roth, Nicole; Cragan, Janet; Moore, Jazmyn; Staples, J Erin; Honein, Margaret; Moore, Cynthia
Abstract: Background: Congenital Zika syndrome (CZS) is a term used to describe the pattern of anomalies in infants due to congenital Zika virus (ZIKV) infection. To date, published reports of infants with these anomalies have been primarily small case series of the most severely affected infants and attempts to determine the CZS phenotype have been based on those reports. Lack of a standard definition has led to inconsistencies in the term's use in the literature and uncertainty about the full spectrum of anomalies, limiting the application for diagnostic and surveillance purposes. Cluster analysis of brain and eye anomalies associated with congenital Zika infection. Clustering occurred independent of laboratory evidence of Zika virus infection, yielding a clinically distinct phenotype associated with congenital infection. Methods: We sought to understand which defects co-occur with possible congenital ZIKV infection using data from 415 mother-infant dyads with laboratory evidence of confirmed or presumptive Zika virus infection from the U.S. Zika Pregnancy and Infant Registry, and a comparison group of 4534 mother-infant dyads with no documented or plausible ZIKV infection from the Zika Birth Defects Surveillance System. We use k-means cluster analysis, discriminant analysis, and regression approaches to identify combinations of defects consistent with possible congenital ZIKV infection. Results: A clinically distinct phenotype emerged as a single cluster in infants for whom both brain and eye defects were recorded that corresponded to evidence of confirmed or probable ZIKV infection. A combination of six defects (sub-cortical calcifications, chorioretinal atrophy/pigmentary anomalies, arthrogryposis or clubfoot, cerebral atrophy or ventriculomegaly, abnormal cortical gyration, and optic nerve atrophy/pallor/other optic nerve abnormalities) predicted the presence of laboratory evidence (area under the receiver operating characteristics curve: 0.95, 95% confidence interval: 0.90–0.99). Conclusion: Further analyses are underway to develop a scoring rubric to weigh evidence of specific congenital anomalies, separately and in combination, that are consistent with laboratory evidence of congenital ZIKV infection. A quantitatively determined spectrum of Zika-associated anomalies, based on the presence of specific combinations of congenital anomalies, will inform a clinical decision tool to improve patient counseling and public health surveillance practices. Disclosures: All Authors : No reported disclosures